2007
DOI: 10.1016/j.neulet.2007.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor gel in shark sense organs?

Abstract: Sharks can sense bioelectric fields of prey and other animals in seawater using an extraordinary system of sense organs (ampullae of Lorenzini) [R.D. Fields, The shark's electric sense. Sci. Am. 297 (2007) 74-81]. A recent study reported that these sense organs also enable sharks to locate prey-rich thermal fronts using a novel mode of temperature reception without ion channels. The study reported that gel extracted from the organs operates as a thermoelectric semiconductor, generating electricity when it is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The measurements of Fields et al, when viewed from the fundamental position of thermoelectric measurement practice, do not support the authors' position [36]. While salt bridges remain the reliable tool of choice for a great span of electrophysiology, they present an unintentionally complicated tool for thermoelectric measurements.…”
Section: Thermoelectric Datamentioning
confidence: 93%
See 3 more Smart Citations
“…The measurements of Fields et al, when viewed from the fundamental position of thermoelectric measurement practice, do not support the authors' position [36]. While salt bridges remain the reliable tool of choice for a great span of electrophysiology, they present an unintentionally complicated tool for thermoelectric measurements.…”
Section: Thermoelectric Datamentioning
confidence: 93%
“…Fields et al reported gel thermoelectricity measurements, from skates, using salt bridge leads and carbon leads [36]. The authors noted artifact concerns with silver electrodes used by Brown in 2003.…”
Section: Thermoelectric Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Notable TE sensitivity was reported [8], whereas further investigation [9] concluded that the TE response is an artifact caused by temperature effects on the measurement electrodes. Such a thermogalvanic (TG) effect is related to the thermally activated electrochemical reactions on electrodes [10]- [12].…”
Section: Introductionmentioning
confidence: 99%